Nature and Sharpness of Regional Development and Modeling of Territorial Management of Bulgaria - Petrov, Kamen (Research Papers, 2019)
The main purpose of the present article is to present and trigger the discussion about the problems of regional development in the present times. An attempt for giving a definition of the specific features and trends in the regional development is made in this article. A comparative analysis of the present status of the regional development sciences is made. Also a methodological assessment of the regional development peculiarities was made as well as the inter-disciplinary relationships with other sciences have been outlined. The foundations of the regional studies have been highlighted and new possible tendencies for the development of this scientific field have been drawn. A mention of the different branches of the regional development studies has been made while a focus on the problems of the urban development and the surrounding environment was put. Also, the problems of the separate territorial communities and the processes of regionalization were analyzed. Last, but not least the article aims at provoking a discussion on the regional development problems and completing the methodology of the regional studies.
Keywords: Regional studies; Regional development; Processes; Methodological; Science; Problems